A Pragmatic Study of Library Management Competencies and Staff Commitment to Service Delivery in a Nigerian University - Ajegbomogun, Fredrick Olatunji (Qualitative and Quantitative Methods in Libraries, 2019)
The study evaluates library management competency and staff commitment to library service delivery in a Nigerian University. The survey method was used to carry out this research. The population for the study comprised heads of section (Senior Librarian-University librarian), para-professionals and other supporting staff in the library. Eighty (80) copies of the questionnaires were administered and fifty-four (54) was duly filled, returned and found valid for analysis. (12 library managers, 42 para-professional/ supporting staff). This represents 67.5% of the total respondents. Similarly, 12 library management staff were sampled representing 100% response rate. The data were analyzed using descriptive statistic and percentages. The finding revealed that leaders are competent enough to transform the library operating system to achieve effective and efficient library service delivery. There is a cordial relationship in the mode of communication in the library from the leaders to the subordinates. Findings also indicated that leaders provide encouragement to his subordinates through constant interactions.